SHR-Zbtb16 minimal congenic strain reveals nutrigenetic interaction between Zbtb16 and high-sucrose diet - Školníková, Elena; Šedová, Lucie; Liška, František; Šeda, Ondřej (Physiological research, 2020)
Both prenatal and postnatal excessive consumption of dietary sucrose or fructose was shown to be detrimental to health and contributing to pathogenesis of metabolic syndrome. Our knowledge of genetic determinants of individual sensitivity to sucrose-driven metabolic effects is limited. In this study, we have tested the hypothesis that a variation of metabolic syndrome-related gene, Zbtb16 (Zinc Finger and BTB Domain Containing 16 will affect the reaction to high-sucrose diet (HSD) content in "matched" nutritional exposition settings, i.e. maternal HSD with re-exposition to HSD in adulthood vs. standard diet. We compared metabolic profiles of adult males of spontaneously hypertensive rats (SHR) and a single-gene, minimal congenic strain SHR-Zbtb16 fed either standard diet or exposed to HSD prenatally throughout gestation and nursing and again at the age of 6 months for the period of 14 days. HSD exposition led to increased adiposity in both strains and decrease of glucose tolerance and cholesterol (Ch) concentrations in majority of low-density lipoprotein (LDL) particle classes and in very large and large high-density lipoprotein (HDL) in SHR-Zbtb16 male offspring. There was a similar pattern of HSD-induced increase of triacylglycerols in chylomicrons and very low-density lipoprotein (VLDL) of both strains, though the increase of (triacylglycerol) TAG content was clearly more pronounced in SHR. We observed significant STRAIN*DIET interactions for the smallest LDL particles as their TAG content decreased in SHR-Zbtb16 and did not change in SHR in response to HSD. In summary, we provide evidence of nutrigenetic interaction between Zbtb16 and HSD in context of pathogenesis of metabolic syndrome.
Keywords: zvířata kongenní; potkani inbrední SHR; Disease Models, Animal; Metabolic Syndrome; modely nemocí na zvířatech; Dietary Sucrose; Pregnancy; Male; Rats; Promyelocytic Leukemia Zinc Finger Protein; sladidla; triglyceridy; Animals, Congenic; Sweetening Agents; Hypertension; nutrigenomika; Animals; Triglycerides; metabolický syndrom; Nutrigenomics; Rats, Inbred SHR; zvířata; Cholesterol; cholesterol; hypertenze; mužské pohlaví; krysa rodu Rattus; ženské pohlaví; těhotenství; Female; protein promyelocytické leukemie s motivem zinkového prstu; konzumní sacharóza